Historical Racist Violence and Intergenerational Harms: Accounts from Descendants of Lynching Victims. (March 2021) - Gaston, Shytierra
African Americans are disproportionately victimized by various forms of racialized violence. This long-standing reality is rooted in America's history of racist violence, one manifestation being racial lynchings. This article investigates the long-term, intergenerational consequences of racial lynchings by centering the voices and experiences of victims' families. The data comprise in-depth interviews with twenty-two descendants of twenty-two victims lynched between 1883 and 1972 in the U.S. South. I employed a multistage qualitative analysis, revealing three main domains of harmful impacts: psychological, familial, and economic. The findings underscore that racist violence has imposed harm beyond victims and for many decades and generations after the violent event. These long-term, intergenerational harms, especially if multiplied across countless incidents, can fundamentally impact the well-being of individuals, families, and communities as well as contribute to structural and macrolevel forces. Findings from this study have implications for research, policy, and practice, including efforts toward redress and reparations.